Caracterização e redução das oscilações espúrias resultantes da representação de linhas de transmissão por meio de elementos discretos de circuitos - Araújo, Anderson Ricardo Justo de [UNESP] (2014)
The solutions of differential equations of a transmission line are generally difficult to obtain due to the complexity of these equations. Considering this characteristics, two models have been proposed to study the electromagnetic transient in transmission line. The first model considers the discrete parameters to represents the transmission line using a cascade of π - circuit and the uses numerical integration methods developed directly in the time domain. The second model considers the distributed parameter of the transmission line. The differential equations in time domain are transformed to algebraic equations in the frequency domain and once obtained the solutions, using Inverse Laplace Transform implemented numerically, the solutions are obtained in the time domain. It was observed the presence of spurious oscillations when a transmission line is represented by a cascade of π-circuits. In this work the spurious oscillations will be analyzed using the simulations obtained from a single and three-phase transmission line. For these analyses, the transmission line is considered with fixed length and represented by different quantities of the π-circuits and the line energized by different voltage sources. It will be designed an analog low-pass filter inserted directly in the lumped parameters transmission line model to reduce spurious oscillations in the simulations, making it more accurate and reliable for the analysis in electromagnetic transients in power systems